Course of iron parameters in HFE‐hemochromatosis patients during initial treatment with erythrocytapheresis compared to phlebotomy. Issue 6 (16th February 2016) - Rombout‐Sestrienkova, Eva; Koek, Ger H.; Neslo, Rabin; van Kraaij, Marian; Menheere, Paul P.; Masclee, Ad; Swinkels, Dorine W.
Abstract : Current treatment for newly diagnosed patients with hereditary hemochromatosis (HH) and iron overload consist of weekly phlebotomy or less frequent and more personalized erythrocytapheresis. Previous observations during phlebotomy suggest an increase in intestinal iron uptake caused by lowering of hepcidin as a result of intensive bloodletting. It is not known whether such an effect is present or even more pronounced using erythrocytapheresis since a larger amount of iron is extracted per procedure. In this study we aimed to assess the effect of erythrocytapheresis on the course of iron parameters, with special focus on serum hepcidin. We performed a retrospective proof‐of‐principle observational study, comparing serum iron parameters in 12 males during the depletion phase using either phlebotomy ( n  = 6) or erythrocytapheresis ( n  = 6). Decreases in serum ferritin over time were similar for both treatments but more pronounced using erythrocytapheresis when expressed per treatment procedure. Hemoglobin did not change during erythrocytapheresis, whereas during phlebotomy decreased with 10%. Increase of erythropoietin and soluble transferrin receptor and decrease in transferrin saturation were similar for both treatments. Reduction in serum hepcidin was higher (50% versus 25% of initial value) and occurred more early using phlebotomy (10 versus 20 weeks after start). In aggregate, compared to phlebotomy, the less frequent and more personalized erythrocytapheresis leads to a more pronounced decrease in serum ferritin per treatment procedure, without a larger decrease in serum hepcidin. This may be clinically relevant and may prevent an increase in intestinal iron uptake and an ensuing vicious circle of more frequent treatment procedures. J. Clin. Apheresis 31:564–570, 2016. © 2015 Wiley Periodicals, Inc.